Canine Mammary Tumors - Breed, Age and Malignant Characteristics as Risk Factors - Tunç, Arda Selin; Sevil Atalay Vural (Acta Scientiae Veterinariae, 2024)
Abstract Background: Canine mammary tumor (CMT) is a benign or malignant neoplasm originating from epithelium, myoepithelium and/or mesenchymal cells of the mammary gland. CMTs are the most often diagnosed neoplasia and age, breed, tumor characterizations as risk factors are important in CMTs. Canine mammary tumors are mostly in the malignant form, not in the benign features. There is a connection between the characters and localizations of the CMT and it frequently occurred in the 3rd, 4th and 5th lobes. These mammary lobes have more malignant characteristics than those in the other lobes, and there is no difference in terms of localization in the right and left lobes This study aimed to identify the variety and the differences occurring of breed, age and tumor characteristics in canine mammary tumors in recent years. Materials, Methods & Results: A total of 165 mammary tumors from 64 bitches were collected and investigated morphologically and histopathologically. The tumors were usually elastic or hard in consistency. The cut surfaces were homogeneous or lobular in appearance and gray-white in color. Most tumors were hard and difficult to cut, so had gray-white bone-like areas on the cut section the histopathological examination of tumors; benign mixed tumor (n = 7), carcinoma in situ (n = 9), simple carcinoma (n = 22), comedocarcinoma (n = 1), mucinous carcinoma (n = 1), carcinosarcoma (n = 114), squamous cell cancer (n = 4), basal cell cancer (n = 1), lipoma (n = 5), fibrosarcoma (n = 1) were diagnosed The formation of CMTs especially malignant tumors was mostly in the 9-12 age range (45.31%). According to the breed of other tumors were distributed as follows: Boxer (n = 15), mongrel (n = 9), German Shepherd (n = 7), Cocker Spaniel (n = 6), Poodle (n = 5), Kangal (n = 4), Rottweiler (n = 2) and Golden Retriever (n = 2), unknown breed (n = 11), Pekingese, Russian Poodle and Labrador retriever (n = 1 each). Half of the cases (50%) were Terrier, and it is followed by the mongrel dogs (12.5%). Malignant CMTs were detected in 95% of Terriers (95/101), while 100% were detected in Cocker Spaniel and Mongrel breeds. Although multiple simultaneous tumors in both the right and left mammary lobes (23/64 = 35.94%), CMTs occurred in the 5th mammary lobe with a rate of 15/64 (23.44%). Benign tumors were noticed less frequently (7.2%) in all mammary tumors, while malignant tumors were much more (92.8%). Of these malignant tumors, 13.3% were simple carcinomas and 69.1% were carcinosarcomas. Out of 64 animals, 23 cases (35.94%) had multiple growths and 41 cases (64.06%) had solitary growths. Lymph node metastases were also detected in 13.16% of them; therefore, benign mixed tumors and carcinosarcomas were excluded from grading for similar reasons, and only simple carcinomas were graded. Since the number of subtypes of simple carcinomas is different from each other and few [tubular type (n = 2), tubulopapillary type (n = 1), papillary type (8) and cystic papillary type (n = 4)], there is no statistically significant difference between the gradings. Discussion: In this study, older age, terrier and mongrel breeds, and medium-sized indicate risk factors for malignancy. Likewise, the occurrence of multiple CMTs should be considered a significant risk factor for the development of malignant mammary tumors. Tumor localization and grading in dogs of various ages and breeds in CMTs were updated and examined in detail in the study. Keywords: bitch, neoplasm, tumor type, grading scores, malignancy, myoepithelial cells, metastases, mammary lobes.